2021
DOI: 10.18433/jpps32116
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Hypertriglyceridemia with Aggressive Continuous Intravenous Insulin

Abstract: Purpose: Severe hypertriglyceridemia requiring hospitalization for intravenous insulin to lower triglycerides and prevent complications of pancreatitis is becoming an increasing problem with little consensus treatment evidence. This is the largest case series to date to evaluate this under-studied area of literature. The objective of this study was to determine the average time to triglyceride lowering less than 500 mg/dL. Methods: This was a retrospective case series from March 2018 to March 2020 at a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Hoff et al described their 23 patient case series in which they demonstrated the e cacy of HDII at a dose of 0.1 units/kg/hr for HTGP, which additionally supports our regarding safety and e cacy. 11 Similarly to Hoff et al, the majority of the patients in our study remained on HDII for approximately 50 hours prior to therapy discontinuation. Although at our institution, there was no formal protocol or guideline, the prescribed HDII dose remained consistent throughout the duration of the infusion until the serum TG levels decreased below 1000 mg/dL.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Hoff et al described their 23 patient case series in which they demonstrated the e cacy of HDII at a dose of 0.1 units/kg/hr for HTGP, which additionally supports our regarding safety and e cacy. 11 Similarly to Hoff et al, the majority of the patients in our study remained on HDII for approximately 50 hours prior to therapy discontinuation. Although at our institution, there was no formal protocol or guideline, the prescribed HDII dose remained consistent throughout the duration of the infusion until the serum TG levels decreased below 1000 mg/dL.…”
Section: Discussionsupporting
confidence: 60%
“…9,10 Case reports and series demonstrated the e cacy of HDII for the treatment of HTGP, with expert consensus recommending a starting dose of HDII between 0.1-0.3 units/kg/hr. 8,11 in this study, we sought to describe our institutional experience with utilizing HDII for the treatment of HTGP to better characterize e cacy and safety of HDII in HTGP.…”
Section: Introductionmentioning
confidence: 99%
“…Being in such a particular period—pregnancy period—with no safe access to other treatment options, patients in our institution were given insulin drip as the related literature demonstrated. ( Jin et al, 2018 ; Hoff and Piechowski, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The authors did not specify how the dextrose-containing fluid was titrated to prevent hypoglycemia, but no hypoglycemic events were reported. In the Hoff and Piechowski 23 case series of 23 patients, 61% of patients achieved a TG level less than 500 mg/dL following administration of a titratable CI-II and dextrose-containing solution. Similar to Yu et al, the authors did not specify how the dextrose-containing fluid was titrated to prevent hypoglycemia but stated there were no hypoglycemic events that prompted discontinuation of the CI-II.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the numerous studies evaluating the use of CI-II in the management of HTG-AP, it remains unknown how to effectively and safely administer CI-II. [13][14][15][16][17][18][19][20][21][22][23][24][25] Consequently, the management is not standardized, and the existing literature does not consistently demonstrate the benefits of using CI-II. Therefore, the purpose of this study was to evaluate the safety and efficacy of a CI-II order set specifically designed for managing HTG.…”
Section: Introductionmentioning
confidence: 99%